The Feynman lectures on physics : - Feynman, Richard Phillips (Addison-Wesley, 1965)
T[hese] books [are] based upon a course of lectures in introductory physics given by Prof. R. P. Feynman at the California Institute of Technology during the academic year 1961-1962; it covers the first year of the two year introductory course taken by all Caltech freshmen and sophormores, and was followed in 1962-63 by a similar series covering the second year.